Determinants of Self-Employment in Ecuador 2017 2018 - García, Alejandra (2021)
Self-employment is considered an essential component within the economy, becoming a potential source of new jobs and a way of employing the population of countries where growing unemployment has become a major economic and social problem. This activity has been practiced over the years as an escape route from the unemployment that citizens have or as a form of entrepreneurship. According to the International Labor Organization (ILO), globally or worldwide, self-employment has increased in the last two decades. On average, 12.4% of workers are self-employed in high-income economies, while in low-income economies this figure rises to 81.9%. This trend has made self-employment a central issue in the labor market. Although self-employment represents a solution for individuals who have few opportunities in the labor sector as employees or dependents, it is also presented as an opportunity for those who seek a different path (entrepreneurship) to their professional career (Simoes et al, 2016) . This last labor sector is considered as a diverse group where individuals start and manage a business, obtaining economic benefits for themselves within different sectors of occupation and industry (Laing, 2011).